HISTORY AND STATUS OF MOOSE IN THE ROSTOV REGION, RUSSIA - Minoranskiy, Viktor A; Sidelnikov, Viktor V; Simonovich, Elena I (Lakehead University, 2009)
Moose (Alces alces) disappeared from the Rostov region in the 19th century due to agricultural development, hunting, and deforestation. They reappeared in the second half of the 20th century due to broad conservation measures including intensive forest management, and by the 1970s numbered >1000 and were found throughout the region. Although hunting was regulated, the population became stagnant in the 1980s presumably from trophy hunting that skewed the sex and age structure, as well as measurable wolf (Canis lupus) predation. Political reform in the 1990s further caused population decline due to increased and less regulated hunting, increased poaching without punishment, reduced predator control, decline in forest management, and large forest fires. Currently the population is at a 50-year low and occupies 1/3 of its range in the 1980s. Moose are no longer considered a commercial species, rather a species of concern.